Pengaruh Konsentrasi Etanol dan Waktu Ekstraksi Terhadap Aktivitas Antioksidan Ekstrak Daun Buangit (Cleome gynandra) Dengan Metode Microwave Assisted Extraction - Krisanta, Clara Sania; Yusasrini, Ni Luh Ari; Kencana Putra, I Nengah (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 4 (2021): Jurnal ITEPA, 2021)
Buangit leaves (Cleome gynandra) contain bioactive components such as phenol compounds, flavonoids and vitamin C, which can act as antioxidant. This research aims were to determine the effect of ethanol concentration and extraction time using Microwave Assisted Extraction (MAE) on antioxidant activity and to obtain the appropriate ethanol concentration and extraction time that can produce the highest antioxidant activity of buangit leaves extract. The research was designed using a completely randomized factorial design, which consisted of two factor. The first factor was ethanol concentration (ethanol 60%, 70%, 80% and 90%) and the second factor was the extraction time (3, 5 and 7 minutes). The entire treatment was repeated 2 times to obtain 24 units of experiments. Data were analyzed by analysis of variance and if the treatment had a significant effect, followed by Duncan Multiple Range Test. This research showed that the interaction between ethanol concentration and time extraction had significant effects on total flavonoids and antioxidant activity, but it had non-significant effects on total phenol and total vitamin C. However, ethanol concentration and time extraction had significant effects on total phenols, total flavonoids, total vitamin C and antioxidant activity. The results showed that MAE of buangit leaves using 70% ethanol concentration for 7 minutes was the best treatment on this research, which can produce 18.52 ± 0.64 mg GAE/g of total phenols, 19.28 ± 0.18 mg QE/g of total flavonoid, 89.85 ± 5.30 mg AAE/g of vitamin C and antioxidant activity based on IC50 value at 131.85 ± 0.71 ppm